Analysis of the use of the Mobile JKN Application on the Waiting Time of Outpatient Services in the Eye Polyclinic at Al-Ihsan Regional Hospital, West Java Province - Cinta, Putik; Setiatin, Sali; Soelistijaningroem, Matoeari; Giatsyal Akbar Sya, Gema (Dinasti Health and Pharmacy Science, 2025)
The purpose of this study was to determine the effect of the Mobile JKN application on the waiting time for outpatient services. Waiting time is the time required by patients from the moment they register at the registration desk until they receive services from health workers, such as entering the examination room or being served by a specialist doctor. The Mobile JKN application is an application for the national health insurance system, which is a form of digital transformation of the business model created by BPJS Kesehatan. This study used a quantitative method with a descriptive approach. The study was conducted at the RSUD Al-Ihsan Jawa Barat in the eye clinic. The sampling technique used the Slovin formula with a sample size of 416. The results of the study show that the minimum waiting time for outpatient respondents at the eye clinic on March 21, 2025, was 5 minutes, and the maximum waiting time for respondents was 262 minutes. The average waiting time for respondents was 70.70 minutes. The minimum waiting time for outpatients at the eye clinic on April 21, 2025, was 4 minutes, and the maximum waiting time for respondents was 179 minutes. The average waiting time for respondents was 63.82 minutes. The minimum waiting time for outpatients at the eye clinic on May 21, 2025 was 1 minute, and the maximum waiting time for respondents was 230 minutes. The average waiting time for respondents was 38.10 minutes. This is in line with the statement that the use of Mobile JKN can help the public to easily complete administrative matters using smartphones anywhere and anytime, but there are still many users who do not use the Mobile JKN application because many people do not understand how to use the Mobile JKN application and not all people have smartphones to access the Mobile JKN application. BPJS Kesehatan is expected to provide education to JKN participants regarding the benefits and added value that can be obtained through the use of the Mobile JKN application.